"Airborne" suture tying technique: Simple steps to make it easy. Issue 12 (30th September 2017) - Agko, Mouchammed; Ciudad, Pedro; Chen, Hung‐Chi
Abstract: A multitude of microsurgical suture techniques have been described. Although accurate apposition and eversion of the vessel ends is paramount for the patency of anastomosis, rapidity is usually of secondary importance. However, in situations in which either multiple anastomoses are required or timely revascularization is crucial, speed becomes a determinant factor for eventual success. "Airborne" suture tying is aimed at decreasing operative time by streamlining the microvascular anastomosis. Over the years, several considerations have emerged as key points for achieving mastery of this helpful maneuver. Herein, we simplify the technique by breaking the maneuver into 2 components: the "charioteer" loop and the "lasso" loop. Relevant literature, indications, and benefits are discussed followed by step‐by‐step descriptions. Both back table and in vivo video demonstrations are presented online.